The Role of Visual Media in Improving the Indonesian Vocabulary of Class II Students of MIS Fathul Munir, Ternate City, Indonesia - Wanisa Rasid; Nurjannah Silswane; Adiyana Adam; M. Mudayana; Abdurrahman Hi Usman (Manunggal Halim Jaya, 2026)
This study aimed to analyze the role of image media in improving the mastery of Indonesian vocabulary among second-grade students of MIS Fathul Munir, Ternate City. The study used a quantitative approach with a quasi-experimental design through a one-group pretest–posttest design. The research subjects were 24 students enrolled in the course. The data collection techniques included vocabulary tests, observations, and documentation. Data were analyzed using the percentage of improvement and Normalized Gain (N-Gain). The results showed that the average score of students increased from 56.25 in the pre-test to 82.08 in the post-test. The percentage of learning completeness increased from 25% to 87.5%, with an N-Gain value of 0.59, which is included in the moderate category. These results indicate that image media play an effective role in improving students' mastery of Indonesian vocabulary. The use of image media also increases students' activeness and learning motivation during the learning process. Thus, image media can be used as an alternative strategy for learning Indonesian vocabulary by lower-grade students of Islamic elementary schools.